1995
DOI: 10.1002/aja.1002020104
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic potential of chick embryonic calvaria: II. Matrix calcium may repress cartilage differentiation

Abstract: Chick embryos cultured in the absence of their eggshell are rendered severely calcium-deficient, and develop a cartilage-like phenotype in the calvarium, a normally osteogenic tissue. In the preceding paper (Jacenko and Tuan [1995] Dev. Dyn. 20213-26), experiments using organ cultured calvaria from day-12 normal and shell-less embryos showed that depletion of calcium alone may be responsible in promoting chondrogenic differentiation in calvaria. Here these findings were extended using an in vivo calvarial graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Consistent with this, we did not see reduced hematopoietic cell outgrowth in cocultures with the IOderived calvarial cells from the ColX-KO mice, presumably due to the lack of/low level of cartilage/ColX production during IO in vivo [52,[63][64][65][66] (Fig. 3).…”
Section: Discussionsupporting
confidence: 74%
“…Consistent with this, we did not see reduced hematopoietic cell outgrowth in cocultures with the IOderived calvarial cells from the ColX-KO mice, presumably due to the lack of/low level of cartilage/ColX production during IO in vivo [52,[63][64][65][66] (Fig. 3).…”
Section: Discussionsupporting
confidence: 74%
“…A number of previous studies have demonstrated that cells throughout the developing bones of the cranium have a chondrogenic potential even though a distinct endochondral phase is never observed during the embryogenesis of these bones 6–8 , 17 , 18 , 54. While many of these studies have identified or have focused on the factors that promote chondrogenesis within the cell populations of the calvaria,15 , 16 , 55 , 56 the underlying relationship of the chondrogenic potential of the cells to the developmental progression of the cranial bones, the contributory role of intrinsic versus extrinsic factors, and the mechanism(s) by which mesenchymal stem cells are restricted into the osteogenic versus the chondrogenic lineage have not been extensively examined. The data presented here indicate that the developmental restriction of skeletal cells of the calvaria is not a result of positive selection for osteogenic differentiation but a negative selection against the progressive growth of chondrogenic cells in the absence of either a permissive or inductive environment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, chondrogenesis is observed within calvaria cell populations in vitro when the growth conditions have been modified to include exogenous factors such OP–115 or dexamethasone,16 suggesting that there are a variety of specific factors which are either permissive or inductive to the chondrogenic process. Finally, in recent studies, calvaria cell populations isolated from 14‐day avian embryos and grown in vitro were shown to produce factors that inhibited limb bud mesenchymal cells from undergoing chondrogenesis while limb bud mesenchymal cells produced factors that stimulated selected calvaria cell populations to undergo chondrogenesis 55 , 56. All these results lead to the conclusion that under normal growth conditions in vivo, osteogenic differentiation predominates as a result of regulated selection against progressive chondrogenic differentiation which is probably under the control primarily of autocrine and paracrine factors produced by the osteogenic calvaria cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this and the accompanying report (Jacenko et al, 1995), we address these questions by examining the differentiation of the chick embryonic calvarium, which has been separated and isolated from its natural tissue and systemic influences, and placed in a n environment of regulated calcium supply. Specifically, our data demonstrate that when calvaria from N and SL embryos are maintained as explants in paired organ cultures with varying calcium concentrations, these tissues can form genuine cartilage in vitro in response to decreased calcium in its milieu.…”
Section: Introductionmentioning
confidence: 99%